PERLINDUNGAN HUKUM TERHADAP MASYARAKAT DI SEKITAR KEGIATAN USAHA PT PERTAMINA GEOTHERMAL ENERGY (PT PGE) HULU LAIS DI KABUPATEN LEBONG DITINJAU DARI ASPEK HUKUM LINGKUNGAN - Tri Andika; Deli Waryenti; Patricia Ekowati Suryaningsih (University Of Bengkulu Law Journal, 2019)
People in several villages in the Lebong Tengah and South Lebong sub-districts of Lebong Regency have recently been anxious because of the landslide in Bukit Beliti which is the site of PT PGE's Hulu Lais cluster A. Landslides resulted in the death of 6 people and other material losses in the form of sinking fish ponds, rice fields and community gardens until crop failure. In addition, the source of drinking water for residents (PDAMs) in the two villages is also polluted, black, foamy and smelly. In the drilling process, PT PGE's machines also issued a loud sound, making the ground vibrate and emitting hot and white steam which caused the surrounding air to become hot. As a result, a number of plants in the surrounding gardens become dry and charred. Finally, in the drilling process PT PGE Hulu Lais also drained water from the Mubai river, so that the river water discharge drastically reduced. As a result, residents who have relied on river water for washing, bathing, irrigating rice fields and fish ponds, must find other water sources. For a civil settlement, PT PGE Hulu Lais has handed over a number of compensation to residents both to residents whose families died and residents whose fields or gardens were submerged in mud. Similarly, the Administration of the Environment Agency (DLH) has given several warnings to PT PGE. However, enforcement of environmental law from the aspect of criminal law has not been implemented due to the absence of PPNS staff in the Administration of the Environment Agency (DLH).